2011
DOI: 10.5301/jn.2011.6247
|View full text |Cite
|
Sign up to set email alerts
|

Good outcomes with Cyclosporine very low exposure with Everolimus high exposure in renal transplant patients

Abstract: Everolimus regimen compared with EC-MPS regimen is associated with lower incidence of DGF, slightly better 1-year graft survival rate, a significantly higher GFR and lower systolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 18 publications
0
37
0
2
Order By: Relevance
“…51,58,59,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153]155 This was because the trial reports failed to explicitly state whether or not all outcomes defined in the study protocol were reported.…”
Section: Completeness Of Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…51,58,59,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153]155 This was because the trial reports failed to explicitly state whether or not all outcomes defined in the study protocol were reported.…”
Section: Completeness Of Trialsmentioning
confidence: 99%
“…The majority of trials (52 maintenance studies, 51,[75][76][77][79][80][81][82][83][84]86,89,[91][92][93][94][99][100][101][102][104][105][106]108,109,[111][112][113][114][116][117][118][119][120][121][122]130,131,133,138,140,141,[144][145][146][147][148][149][151][152][153]155 nine induction studies, [71][72][73]…”
Section: Treatment Allocation Masked From Outcome Assessorsmentioning
confidence: 99%
See 3 more Smart Citations